Determining of the laser heat flux for three-dimensional conduction model by the sequential method - Long, Nguyen Nhat Phi; Nguyen, Son Hoai; Quan, Nguyen (Vietnam Journal of Mechanics, 2020)
When performing a laser processing, one of the parameters to consider is the laser heat flux. This is a very important parameter of the processing. It is difficult to directly and correctly measure this parameter during the processing. Therefore, to estimate this parameter, a solution has been implemented. In this study, the Newton–Raphson method has been calibrated as an operational algorithm to evaluate the laser heat flux value accurately in the 3-D conduction model. The outstanding features in this algorithm: the unaware absorption coefficient's functional form is no preset, and the nonlinear least-squares are no necessary. To confirm the effectiveness of the presented method, the paper has given two specific applications. Indeed, in this research, based on the results that have been achieved in two illustrations, the sequential method to determine the inversely laser heat flux in the three-dimensional conduction model is a reasonable, correct, and powerful method.